Metabolic Engineering of Escherichia coli for the Production of Hyaluronic Acid From Glucose and Galactose - Woo, Ji Eun; Seong, Hyeon Jeong; Lee, Sang Yup; Jang, Yu-Sin (Frontiers in Bioengineering and Biotechnology, 2019)
Hyaluronic acid is a glycosaminoglycan biopolymer widely present throughout connective and epithelial tissue, and has been of great interest for medical and cosmetic applications. In the microbial production of hyaluronic acid, it has not been established to utilize galactose enabling to be converted to UDP-glucuronic acid, which is a precursor for hyaluronic acid biosynthesis. In this study, we engineered Escherichia coli to produce hyaluronic acid from glucose and galactose. The galactose-utilizing Leloir pathway was activated by knocking out the galR and galS genes encoding the transcriptional repressors. Also, the hasA gene from Streptococcus zooepidemicus was introduced for the expression of hyaluronic acid synthase. The consumption rates of glucose and galactose were modulated by knockout of the pfkA and zwf genes, which encode 6-phosphofructokinase I and glucose-6-phosphate dehydrogenase, respectively. Furthermore, the precursor biosynthesis pathway for hyaluronic acid production was manipulated by separately overexpressing the gene clusters galU-ugd and glmS-glmM-glmU, which enable the production of UDP-glucuronic acid and UDP-N-acetyl-glucosamine, respectively. Batch culture of the final engineered strain produced 29.98 mg/L of hyaluronic acid from glucose and galactose. This study demonstrated the production of hyaluronic acid from glucose and galactose in the engineered E. coli.